Kajian Fonologi: Analisis Perubahan Bunyi Bahasa pada Anak Penderita Down Sindrom - Aryanti, Wiwit; Putria, Najhwa Tsalisa; Madinah, Nur (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2025)
Children with Down Syndrome are known to have physical impediments such as a small mouth size, a large tongue (macroglossia), and abnormal jaw and nasal cavity structures. These physiological factors affect the articulation process and sound production, thus directly impacting the clarity and accuracy of their speech. In this study, we detail how children with Down Syndrome pronounce words in Indonesian, focusing on the phoneme sound changes that occur during the speech production process. The sound changes can include omissions (zeroization), which means that one or more phonemes in a word are not pronounced the addition of sounds (anaptyxis), which is the emergence of new phonemes that are not found in the standard form of words; the exchange of sound positions (metathesis), where the order of phonemes in a word changes; and the simplification of diphthongs (monophthongization), which is the pronunciation of diphthongs as a single vowel. The results of the analysis indicate that the phonemic sound changes that occur not only reflect the physiological limitations of these children but also serve as their adaptive strategies in communication. In other words, these phonological changes can be seen as efforts by children to simplify articulation so that they can still convey messages effectively, even if not always consistent with the standard phonological forms of Indonesian. These variations illustrate the complexity of the phonological processes that are characteristic of this population, and provide important insights for the fields of speech therapy, inclusive education, and clinical linguistics.